Substrate specificity of the cyclic AMP-dependent protein kinase. - Kemp, B E (1975)
The protein substrate specificity of the catalytic subunit of rabbit skeletal muscle cyclic AMP-dependent protein kinase (EC 2.7.1.37; ATP:protein phosphotransferase) has been studied using genetic variants of beta casein. It was found that beta casein-B was phosphorylated at a much greater rate than beta caseins A1, A2, A3, or C. The enhanced phosphorylation of beta casein-B, as compared with the most common variant A2, was attributed to an arginine substitution for a serine at position 122, which caused a nearby residue, serine 124, to become a phosphorylation site for the protein kinase. These results further support the concept that the local primary structure is important in specificity and that arginine may be a specific determinant common to all the local phosphorylation site sequences recognized by the cyclic AMP-dependent protein kinase.